Keizer tussen stropdragers : Karel V 1500-1558 - Dambruyne, Johan, 1965-; De Zutter, Joris; Decavele, Johan, 1943-; Heymans, Frans, 1938-2018 (Leuven : Davidsfonds, 1990)
KK en Gent
Includes bibliographical references (p. 229-236) and index.
Keywords: Ghent (Belgium) -- History -- 16th century; Netherlands -- Civilization -- 16th century; Netherlands -- History -- Charles V, 1506-1555.